Introduction: youth political participation in a transition society - Allaste, A.-A. (2016)
This special issue of Studies of Transition States and Societies focuses on youth political participation in Estonia. The articles explore different dimensions of participation, providing examples of how politics is practiced by young people in a society that has undergone a relatively recent and substantial social, economic and political transformation: the shift from being an integral part of the Soviet Union to full membership of the European Union. This transition is reflected in changing patterns of activism among Estonian youth and the nature of the issues with which they engage, with participation influenced by, one the one hand, the legacies of the communist period and, on the other, the challenge of living in contemporary Europe. While rooted in established theoretical frameworks, this discussion is informed by a strong empirical evidence base. We concentrate on discussing fi ndings from a recently completed European Commission funded study entitled Memory, Youth, Political Legacy and Civic Engagement (MYPLACE). As its title suggests, this four-year project, conducted during 2011-2015, looked at youth political activism and civic engagement, integrating research teams from 14 diff erent regional contexts across Europe, including Estonia. While the contributions that follow concentrate on the Estonian context, a closing article refl ects on the meaning of our results within the broader framework of European society, building on the work of our international colleagues. We begin, however, in this introduction with an outline of what we regard as some of the key theoretical perspectives on political participation and signifi cant features of our Estonian research context.